2004
DOI: 10.1590/s0034-70942004000400003
|View full text |Cite
|
Sign up to set email alerts
|

Clonidina e dexmedetomidina por via peridural para analgesia e sedação pós-operatória de colecistectomia

Abstract: J U S T I F I C AT I VA E O B J E T I V O S : A c l o n i d i n a e a dexmedetomidina são agonistas alfa 2 -adrenérgicos que, q u a n d o a d m i n i s t r a d o s p o r v i a p e r i d u r a l , p o s s u e m propriedades analgésicas e potencializam os efeitos dos anestésicos locais. A presente pesquisa objetivou avaliar a analg e s i a e a s e d a ç ã o p r o d u zi d a s p e l a c l o n i d i n a o u dexmedetomidina associadas à ropivacaína, por via peridural, no pós-operatório de colecistectomia por via su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Some of the studies have noted dexmedetomidine-associated decreases in heart rate and blood pressure 8,34 and increased sedation. 32,33 The other four studies found no differences in side effects associated with dexmedetomidine. The sedation associated with intravenous dexmedetomidine has been termed “cooperative sedation,” which may mean that any sedation from perineural administration may be beneficial, especially when compared with the type of sedation associated with benzodiazepines and opioids.…”
Section: Discussionmentioning
confidence: 88%
“…Some of the studies have noted dexmedetomidine-associated decreases in heart rate and blood pressure 8,34 and increased sedation. 32,33 The other four studies found no differences in side effects associated with dexmedetomidine. The sedation associated with intravenous dexmedetomidine has been termed “cooperative sedation,” which may mean that any sedation from perineural administration may be beneficial, especially when compared with the type of sedation associated with benzodiazepines and opioids.…”
Section: Discussionmentioning
confidence: 88%
“…Dexmedetomidine, although currently approved for IV use only, has been successfully used in neuraxial blocks in experimental and clinical studies without neurological deficits encouraging its use by the epidural route. [ 13 19 20 21 ] Nevertheless, there are still some concerns regarding its safety. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, an α 2 -agonist for α 2 -adrenergic receptors, possesses sedative and analgesic properties without respiratory depressant effect [1] and enhances their effects without increasing the incidence of side effects when added to local anesthetic agents [28]. At present, dexmedetomidine, although approved for intravenous use only, has been successfully used in neuraxial block and epidural block in experimental and clinical studies with less side effects [9, 10]. However, the study of dexmedetomidine is scarce in the obstetric population, and the optimal dose of epidural dexmedetomidine combined with ropivacaine for labor analgesia is still uncertain.…”
Section: Introductionmentioning
confidence: 99%